Age-Related Mechanisms of Cricoid Cartilage Response to Injury in the Developing Rabbit - Cherukupally, Shilpa Reddy; Adams, Allison B.; Mankarious, Leila A. (The Laryngoscope, 2003)
Objective To evaluate age‐related mechanisms of cricoid cartilage response to injury in an animal model. Study Design A pilot study using monoclonal antibodies to chondrocyte proliferation markers collagen II, aggrecan, and proliferating cell nuclear antigen (PCNA) to evaluate age‐related response of injured cricoid cartilage. Methods Twenty‐seven New Zealand white rabbits aged 4 weeks, 8 weeks, and 1.5 years were studied. Six animals in each age group underwent intracartilaginous injury through cricofissure and tracheofissure. Three animals of each group were used as control subjects. The animals were killed 4 weeks after injury, their cricoid cartilages harvested, and 7‐μm sections of tissue obtained. The cricoid tissue sections were stained with immunofluorescent monoclonal antibody markers to collagen II, aggrecan, and PCNA. Results In all age groups, no control animals had symptoms of airway compromise or immunohistochemical abnormality. For all three markers of chondrocyte proliferation, the 4‐week‐old animals showed markedly increased staining at the injured edges of cartilage. The 8‐week‐old animals showed mild increased extracellular staining, and the 1.5‐year‐old animals showed no increased staining compared with uninjured areas of the cricoid ring and with control animals. Conclusion There was a progressive, age‐related attenuation of staining for markers of chondrocyte proliferation in the 8‐week and 1.5‐year‐old rabbits compared with the 4‐week‐old rabbit cricoids.